2021
DOI: 10.3389/fped.2021.746471
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Reference Database for Typical Body and Organ Growth of the Artificially Reared Pig as a Biomedical Research Model

Abstract: Objectives: The pig is a common model utilized to support substantiation of novel bioactive components in infant formula. However, reference ranges for outcomes to determine safety are unclear. Our objective was to use historical data to objectively define typical body and organ growth metrics of the domesticated pig in research.Methods: Twenty-two studies were compiled to assess typical growth of body and organ weights in young pigs. Metadata were organized to include milk replacer sources, bioactive componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
2
0
0
Order By: Relevance
“…Furthermore, the similar observations in body weight and kcal intake throughout the experiment between the dairy-based and plant-based formula fed animals showed that the plant-based formula utilized in the current study also supported adequate growth in those piglets. The daily body weight measured in all the piglets was in line with the growth reported in sow-fed piglets during the neonatal phase [ 22 , 23 , 24 ] or soy-fed piglets reported by others [ 25 ], and in line with our previous findings, in which piglets received pasteurized human milk, dairy-based milk formula or sow-fed piglets [ 26 ]. Additionally, the gastrointestinal tract development as well as that of the organs examined were similar between both dietary groups and are comparable with neonatal piglets that received a dairy-based milk formula [ 27 ] or soy formula [ 28 ] for 21 days.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the similar observations in body weight and kcal intake throughout the experiment between the dairy-based and plant-based formula fed animals showed that the plant-based formula utilized in the current study also supported adequate growth in those piglets. The daily body weight measured in all the piglets was in line with the growth reported in sow-fed piglets during the neonatal phase [ 22 , 23 , 24 ] or soy-fed piglets reported by others [ 25 ], and in line with our previous findings, in which piglets received pasteurized human milk, dairy-based milk formula or sow-fed piglets [ 26 ]. Additionally, the gastrointestinal tract development as well as that of the organs examined were similar between both dietary groups and are comparable with neonatal piglets that received a dairy-based milk formula [ 27 ] or soy formula [ 28 ] for 21 days.…”
Section: Discussionsupporting
confidence: 90%
“…These results are congruent with previous studies, which also indicated a lack of difference in overall growth performance due to supplementation of 3ˊ-SL or 6ˊ-SL in pigs ( 16 , 17 , 23 , 35 ). In terms of body tissues, brain and liver weights for all treatments at PND 33 were also similar to those from previous studies ( 16 , 17 , 36 ). Despite 6ˊ-SL pigs having heavier absolute brain weights at PND 61, brain and liver weights relative to body weight did not differ by dietary treatment, which indicates similarities in allometric organ growth.…”
Section: Discussionsupporting
confidence: 86%